California statewide model for high-speed rail - Maren Outwater; Kevin Tierney; Mark Bradley; Elizabeth Sall; Arun Kuppam; Vamsee Modugala (Journal of Choice Modelling, 2010)
The California High Speed Rail Authority (CHSRA) and the Metropolitan Transportation Commission (MTC) have developed a new statewide model to support evaluation of high-speed rail alternatives in the State of California. This statewide model will also support future planning activities of the California Department of Transportation (Caltrans). The approach to this statewide model explicitly recognizes the unique characteristics of intraregional travel demand and interregional travel demand. As a result, interregional travel models capture behavior important to longer distance travel, such as induced trips, business and commute decisions, recreational travel, attributes of destinations, reliability of travel, party size, and access and egress modal options. Intraregional travel models rely on local highway and transit characteristics and behavior associated with shorter distance trips (such as commuting and shopping).
Keywords: 330; discrete choice models; interregional; high-speed rail; induced demand; ridership forecasting; trip frequency; destination choice; mode choice